MEANINGFUL LEARNING IN THE PERSPECTIVE OF INFORMAL ECONOMIC EDUCATION - Hasan, Muhammad; Kamaruddin, Citra Ayni; Nurdiana, Nurdiana; Nurjannah, Nurjannah; Elpisah, Elpisah (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2023)
Abstract: This study aims to determine the informal economic education in the family through the habit of saving for children, which results in meaningful learning. This study uses a qualitative approach. The data collection techniques used in this study were observation and interviews. The informants in this study were five parents and five children in urban farming family households in Makassar City. The data obtained in this study will be analyzed using data coding techniques. The results of this study indicate that (1) parents have understood their children from an early age regarding informal economic education, especially saving; (2) the formation of knowledge, attitudes, and saving behavior makes children feel that parents have a role in guiding and teaching them about saving, which later became a meaningful learning for children and continues to stick in their memories to this day; and (3) the freedom given by parents and the absence of coercion to save are also meaningful lessons that are embedded in children's memories. Abstrak: Penelitian ini bertujuan untuk mengetahui pendidikan ekonomi informal yang berlangsung di dalam keluarga melalui pembiasaan menabung kepada anak yang menghasilkan pembelajaran bermakna. Kajian ini menggunakan pendekatan kualitatif. Informan dalam penelitian ini adalah 5 orang tua dan 5 anak pada rumah tangga keluarga petani perkotaan di Kota Makassar. Data yang diperoleh dalam penelitian ini akan dianalisis dengan mengunakan teknik coding data. Hasil penelitian ini menunjukkan bahwa (1) para orang tua sejak dini telah memahamkan kepada anak terkait pendidikan ekonomi informal khususnya menabung, (2) pembentukan pengetahuan, sikap, dan perilaku menabung membuat anak merasakan bahwa orang tua mempunyai peran dalam membimbing dan mengajarkan mereka terkait menabung, yang kemudian hal tersebut menjadi pembelajaran yang bermakna bagi anak dan terus melekat di ingatan mereka hingga saat ini; dan (3) adanya kebebasan yang diberikan oleh orang tua dan tidak adanya paksaan untuk menabung juga menjadi pembelajaran bermakna yang melekat dalam ingatan anak.